Analisis Rancang Bangun Sistem Repositori Institusi Berbasis Metadata Dublin Core di UKDW Yogyakarta - Antonius Rachmat C. (Universitas Multimedia Nusantara, 2014)
In this paper we will discuss how to design and analysis a repository system in university, Duta Wacana Christian University (DWCU). The system is web-based, and implements Dublin Core (DC) metadata, using tagging systems, and implements Open Archive Initiatives-Protocol for Metadata Harvesting (OAI-PMH) data provider. The term Institutional Repository (IR) appears since 2003 and is now widely used in various institutions including universities. IR university is a place that contains digital work data, both scientific and non-scientific research from entire academic community of the university. IR univesitry contains many formats such as documents (text), audio (sound), and video. Development of the system has been conducted by the author and team and produce a repository that has appropriate permissions to the stored data, it is applying the standard DC metadata and tagging on each of its file, it has preview feature, and able to perform searching based on tag and DC metadata that previously stored in it. The results concluded that implementation of DC metadata that store permanently in each file, causes each file has a unique metadata signature, so that each file downloaded from the system is actually (originally) comes from UKDW institutional repository. The use of tagging on each file allows categorization and retrieval based on tags, and OAIPMH protocol implementation allows IR data provider collaborate and integrate with other OAI-PMH systems, such as Portal Garuda that owned by Indonesian Higher Education (DIKTI). Index Terms - Institutional Repository (IR), metadata, Dublin Core (DC, tagging, OAI-PMH data provider.